Exploring High School Students’ Perception of Using ChatGPT in Learning English - Wulandari, Agustina Nurul; Setiyono, Junaedi; Ngafif, Abdul (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2025)
This study aimed to explore students’ perceptions of using ChatGPT as a learning aid in English language instruction for tenth-grade students at Madrasah Aliyah Negeri Purworejo in the 2024/2025 academic year. A qualitative approach with a case study design was employed. Data were collected through a closed-ended questionnaire consisting of twenty statements covering aspects such as vocabulary, grammar, pronunciation, motivation, self-confidence, ease of use, and learning preferences. A total of 69 students from classes X-G and X-H participated in this study. The data were analyzed descriptively to identify patterns in students’ perceptions of ChatGPT usage. The results showed that most students had positive perceptions. They believed that ChatGPT helped improve vocabulary and grammar, enhanced pronunciation, boosted motivation and confidence, and made English learning more enjoyable. Although some students reported doubts or minor technical issues, overall, ChatGPT was perceived as an effective and engaging tool for supporting English language learning. Therefore, ChatGPT is recommended as a complementary learning aid to enhance classroom instruction.